(untitled) (Eurasian Medical Research Periodical, 2022)
Neuralgia of the trigeminal nerve is characterized by severe painful attacks, the mechanism of formation of which is described in numerous literary sources, where the authors describe various pathogenetic concepts with the development of treatment methods. This work is no exception, the study was conducted on the basis of a private clinic, studying the clinical and pathogenetic aspects in elderly and senile patients, observing the stage of diagnosis; laboratory and instrumental parameters were studied, where the deformation of the trigeminal nerve orifices by osteoporosis was proved. The cause itself was determined to be compression-tunnel; optimization of treatment with chondroprotective drugs showed high positive results